Assessment of Antidermatophytic Activity and chemical composition of Nigerian Citrus senensis (L.) Osbeck Essential Oil against Multidrug-Resistant Pathogenic dermatophytes Isolated from Tinea capitis Samples - Hussain Y. Ungo-kore; Joseph Ehinmidu; Josiah Onaolapo; Olayeni Olonitola (Ain Shams University, 2021)
Many conventional antifungal agents are becoming ineffective against resistant strains of dermatophytes and as such the use of essential oil (EO) may confer a possible panacea to fight against such multidrug-resistant dermatophytes. This study is aimed at determining the antidermatophytic activity of EO from fruit peel of Nigerian Citrus senensis (L.) Osbeck against multidrug-resistant (MDR) tinea capitis dermatophytes and possible chemical composition. The EO was reaped by hydro-distillation and the chemical composition was investigated using gas chromatography/ mass spectroscopy (GC-MS).The antidermatophytic activity was evaluated using agar diffusion method against four dermatophyte strains (Two MDR dermatophytes, one referenced strain and one susceptible).The minimum inhibitory and fungicidal concentrations (MIC/MFC) were determined by agar dilution methods. The major components were terpenes: - D-Limonene (26.64 - 63.27%), α-terpineol (2.38 - 39.36%), β-linalool (2.28 - 13.42%), Carveol (1.36 - 3.91%), Carvone (3.62 - 3.80%) and α-Farnesene (1.29-1.83 %). Other non terpenes include 2,3,4,5-Tetrahydropyridazine (0.83%). The test results revealed EO to be active against all strains.The EO subjected to boiling temperature (100 0C) had increased amount of α-terpineol, β-Linalool, Carveol, Carvone and other imaginative compounds such as 1-Octanol (Heptyl carbinols) with increased antidermatophytic activity (inhibition diameters from 16.00 ± 0.00 - 22.67 ± 0.33 mm at a dilution of 1/16). To the best of our knowleged, this is the first description of the activity of Citrus senensis (L.) Osbeck fruit EO against multidrug-resistant tinea capitis dermatophytic strains. Our study suggests that this EO could be used clinically to treat or prevent dermatophytic infections with multidrug-resistant strains.